3rd Symposium of applied science for young researchers: short papers - Fernandes, Florbela P. (Ed.) (2023)
These are the short papers proceedings of the 3rd Symposium of Applied Science for Young Researchers – SASYR. This scientific event welcomed works by junior researchers on any research topic covered by the following three research centers: ADiT-lab (from IPVC, Instituto Politécnico de Viana do Castelo), 2Ai (from IPCA, Instituto Politécnico do Cávado e do Ave) and CeDRI (from IPB, Instituto Politécnico de Bragança). The main objective of SASYR is to provide a friendly and relaxed environment for young researchers to present their work, discuss recent results, and develop new ideas. In this way, this event offered an opportunity for the ADiT-lab, 2Ai, and CeDRI research communities to gather synergies and promote collaborations, thus improving the quality of their research. The SASYR 2023 took place at Instituto Politécnico do Cávado e do Ave, Barcelos, Portugal, on the 11th of July, 2023.